2006
DOI: 10.1097/01.psy.0000221227.02975.a0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Effort-Reward Imbalance on Inflammatory and Cardiovascular Responses to Mental Stress

Abstract: These findings suggest that the association between chronic work stress and cardiovascular disease risk may be mediated in part by heightened acute inflammatory responsivity. These responses appear not to result from differences in sympathoadrenal activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 53 publications
3
34
0
1
Order By: Relevance
“…A dysregulated secretion pattern was observed in a majority of these studies [32,[34][35][36]. In view of the importance of inflammation for the development of cardiovascular disease [37] a recent experimental study is of particular interest documenting higher concentrations of C-reactive protein (a marker of inflammation) following exposure to a standardized mental stress test in participants scoring high on ERI measures, compared to participants with less or no work stress [38]. Finally, a summary index of stress-related biological markers of 'allostatic load' has been proposed by McEwen [31], indicating increased susceptibility to cardiovascular risk and disease.…”
Section: Methodsmentioning
confidence: 99%
“…A dysregulated secretion pattern was observed in a majority of these studies [32,[34][35][36]. In view of the importance of inflammation for the development of cardiovascular disease [37] a recent experimental study is of particular interest documenting higher concentrations of C-reactive protein (a marker of inflammation) following exposure to a standardized mental stress test in participants scoring high on ERI measures, compared to participants with less or no work stress [38]. Finally, a summary index of stress-related biological markers of 'allostatic load' has been proposed by McEwen [31], indicating increased susceptibility to cardiovascular risk and disease.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular readings continued during two 5 min standardised behavioural challenges in random order: a mirror tracing task and a socially evaluating speech task, which have been described previously (Hamer et al, 2006). In the speech task participants were given a hypothetical scenario in which they had to verbally defend themselves against the threat of unemployment.…”
Section: Methodsmentioning
confidence: 99%
“…Acute mental stress has been shown to induce increases in circulating inflammatory markers such as interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) (44) and these responses are more pronounced in participants with enduring chronic stress and depressive symptoms (45,46), although less pronounced in physically fit participants (47). Numerous studies have also demonstrated elevated concentrations of various inflammatory markers at rest in differing populations reporting depressive symptoms (48).…”
Section: Physical Activity Stress and Inflammationmentioning
confidence: 99%